The Influence Of Knowledge Management And Innovation Capability On Small Business Performance Through Competitive Advantage Mechanism - Erni Dewi Munte; Sarman Sinaga; Lennaria Lusia Tarigan; Afrida Yanti Surbakti; Orniawati Lestari Waruwu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continues to increase, yet many still face challenges in business management, particularly in implementing knowledge management, fostering innovation capability, and building competitive advantage. This study investigates the influence of knowledge management and innovation capability on MSME performance, with competitive advantage and innovation capability as mediating variables. Data were collected from 329 MSME respondents in Medan City using purposive sampling and analyzed using Structural Equation Modeling (SEM) with AMOS version 26 and Sobel test for mediation analysis. The findings reveal that both knowledge management and innovation capability significantly affect MSME performance. Knowledge management also has a significant impact on both competitive advantage and innovation capability. However, innovation capability does not significantly influence competitive advantage. Furthermore, while competitive advantage directly affects MSME performance, it does not mediate the relationship between knowledge management or innovation capability and performance. In contrast, innovation capability successfully mediates the effect of knowledge management on performance. These results highlight the strategic importance of strengthening knowledge management and innovation capability to enhance MSME sustainability and competitiveness. Keywords: Knowledge Management, Innovation Capability, MSME Performance, Competitive Advantage